2018
DOI: 10.1002/iroh.201701923
|View full text |Cite
|
Sign up to set email alerts
|

High food availability linked to dominance of small zooplankton in a subtropical floodplain

Abstract: Zooplankton body size is fundamentally affecting productivity, ecosystem respiration, nutrient cycling, and energy transfer and may be controlled by food availability but also water physical and chemical characteristics. However, the differences in control of water physical and chemical characteristics and food availability on zooplankton body size have rarely been investigated in subtropical systems. We tested the hypotheses that: (i) the type of environment, food availability, and water physical and chemical… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
10
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 20 publications
(11 citation statements)
references
References 60 publications
(103 reference statements)
1
10
0
Order By: Relevance
“…The river water carried mineral and organic suspension into the connected lakes, thus providing food for detritivorous rotifera, such as K. tecta or B. angularis. Similar phenomena are observed by Bomfim et al [53].…”
Section: Discussionsupporting
confidence: 90%
See 1 more Smart Citation
“…The river water carried mineral and organic suspension into the connected lakes, thus providing food for detritivorous rotifera, such as K. tecta or B. angularis. Similar phenomena are observed by Bomfim et al [53].…”
Section: Discussionsupporting
confidence: 90%
“…According to Mitrovic et al [52] organic matter supply from inundation could stimulate heterotrophic bacterioplankton and affect zooplankton density and structure. High food availability is related to greater density of zooplankton, which is dominated by small-sized rotifers [53], e.g., K. tecta (Table 3, Figure 4B). Rotifers preferred the transitional floodplain lake ( Figure 5A).…”
Section: Discussionmentioning
confidence: 99%
“…This was probably because each guild encompasses different feeding strategies and habitat preferences (Oh et al, 2017). For example, filter feeders (trophi: malleate, malleoramate, and ramate) represent smaller bodied rotifers, ingest multiple food items (but no larger than ∼15-20 μm), are predominantly planktonic (Karabin, 1985;Obertegger & Manca, 2011), and good competitors under high food availability (Bomfim et al, 2018;Obertegger & Manca, 2011).…”
Section: Discussionmentioning
confidence: 99%
“…The species identification followed Koste (1978) and Segers (1995). We also obtained the body length of each species from the literature (Bomfim et al, 2018;Koste, 1978;de Souza Magalhães Braghin, 2018). We found 8 types of trophi among the 234 species identified such as malleate, malleoramate, ramate, virgate, uncinate, cardate, incudate, and forcipate (Figure 3).…”
Section: Field Sampling and Laboratory Analysismentioning
confidence: 99%
“…According to Sampaio et al (2002) and Rietzler et al (2002) these species, of large size, can be used as indicators of trophic state in freshwater ecosystems. Studies have demonstrated a relationship between body size of aquatic organisms and availability of feeding resources (Jeppesen et al 2010, Bomfim et al 2018, Mantovano et al 2019. Habitats with high productivity have a higher quantity of available energetic resources (Ortega-Mayagoitia et al 2011).…”
Section: Discussionmentioning
confidence: 99%